Elektroplating Grafena-Polianilina pada Stainless Steel sebagai Elektroda pada Elektrolisis Air untuk Produksi Hidrogen: Electroplating of Graphene-Polyaniline on Stainless Steel as Electrodes on Water Electrolysis for Hydrogen Production - Rahmiani Gani; Syarifah Rabiatul Adawiah; Arfiani Nur (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2021)
Hydrogen production by water electrolysis can be optimalized by improve the working electrode. Stainless steel as working electrode was coated with graphene and polyaniline by using cyclic voltammetry method with Ag/AgCl as reference electrode and Pt as counter electrode. Coated electrodes were characterized by SEM-EDS and cyclic voltammetry method. Furthermore, the synthesized electrode was applied for water electrolysis by adding 1- 5 g/L NaHCO3. The characterization data showed that Stainless steel/Graphene-Polyaniline electrode can be synthesized by using cyclic voltammetry. The coating process was conducted at sweeping rate 10 mV/s on voltage -0.2 to 0.8 V for 10 cycles. The voltammograms showed that the highest cathodic peak current of electrolysis obtained at 0.491 mA by addition 2 g NaHCO3 on SS/G-PANi0,5 electrode, and the highest anodic peak current obtained at 0.191 mA by addition 2 g NaHCO3 on SS/G-PANi0,5 electrode. Based on the overpotential data, the smallest average potential difference of H+ adsorption obtained by SS/G-PANi1,0 electrode, and the smallest average potential difference of H+ desorption obtained by SS/G-PANi0,5 electrode. Keywords: Stainless steel, hydrogen production, electroplating, electrocatalyst, electrolysis